Ethnoscience and Web-based Learning Media to Maintain Cultural Awareness in Science Classroom: An Exploratory Sequential Study - Naila, Ishmatun; Kusumajanti, Wahju; Anggraini, Ade Eka (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
This research aimed to measure prospective teachers' cultural awareness in learning using web and ethnoscience-based media. Then, to confirm the me-dia's feasibility, we conducted teaching material verification tests and media verification tests utilizing Borg Gall theory. A mixed method study was used in data collection techniques, including observations, documentation, and interview. Following the qualitative, quantitative verification test was conducted by two verifiers, with the first verifier, media professionals, rated highly effective with an average of 96.6%. In contrast, the average percent-age of material expert verifiers was 98%, rated highly effective. The results showed that the student's cultural knowledge increased statistically signifi-cantly with 5% alpha after learning science using the media. The average n-gains for the three grades were high, with no differences among the three grades, and over 93% of students responded positively to the media. Ethno-science and web-based learning media meet the media eligibility criteria: val-id, practical, and effective to improve students' cultural awareness in science classrooms.